Reality, reason, and rights : essays in honor of Tibor R. Machan - Machan, Tibor R.; Rasmussen, Douglas B., 1948-; Skoble, Aeon J.; Den Uyl, Douglas J., 1950- (Lexington Books, 2011)
This collection of essays seeks to explore Tibor R. Machan's philosophical ideas by considering some of the basic issues with which he has been concerned throughout his long and highly productive career.